Understanding low field microwave absorption in Ni-Mn based Heusler alloy films. (November 2021) - Modak, Rajkumar; Srinivasan, Ananthakrishnan; Srinivasu, Vallabhapurapu Vijaya
Highlights: First demonstration of low field microwave spectra (LFMA) in Heusler alloy. LFMA spectra show hysteresis under cyclic field similar to the Magnetization. LFMA hysteresis varies with applied field angle in a correlated manner with Coercivity. The LFMA governed by same process as Magnetization loop in Heusler alloys. Abstract: Low field microwave absorption (LFMA) signal has been observed for the first time in room temperature microwave spectra recorded at 9.44 GHz in polycrystalline Ni-Mn-Sn Heusler alloy films. The observed LFMA spectra is different from conventional ferromagnetic resonance and poses hysteresis near the zero field region of the spectrum. The observed LFMA spectra can be well correlated with the isothermal magnetization ( M – H ) loops recorded at different film orientations to the applied dc magnetic field from 0° to 90°. Furthermore, with small Fe, Co substitution in Ni-Mn-Sn film, both LFMA signal as well as the M – H loop properties of these films varied in a correlated manner, signifying a strong dependence of LFMA on the magnetization process in these films. The demonstration is useful both for fundamental and application point of view for characterization of magnetic materials and explore their applications in microwave assisted nanoelectronic devices. Graphical abstract: Image, graphical abstract